Reality is broken : why games make us better and how they can change the world - McGonigal, Jane, ....- (London : Vintage, 2012)
We are living in a world full of games. More than 31 million people in the UK are gamers. The average young person will spend 10,000 hours gaming by the age of twenty-one. The future belongs to those who play games. In this ground-breaking book, visionary game designer Jane McGonigaI challenges conventional thinking and shows that games - far from being simply escapist entertainment - have the potential not only to radically improve our own lives but to change the world.